A zeolite as a tool for successful refolding of PEGylated proteins and their reassembly with tertiary structures. (3rd June 2019) - Sonotaki, Seiichi; Noguchi, Keiichi; Yohda, Masafumi; Murakami, Yoshihiko
Abstract: In the present study, we demonstrated zeolites' potential contribution to establish a method for preparing successfully refolded and reassembled PEGylated protein nanoparticles without the use of protein denaturants through the proteins' reassembly process. At first, the PEGylated nanoparticles are disassembled into identical PEGylated protein subunits by means of protein denaturants, and then the denatured subunits are adsorbed to zeolites. After the complete removal of denaturants, high‐molecular‐weight poly(ethylene glycol) (PEG) molecules are added to a solution where the zeolites suspend. Consequently, the PEGylated proteins are gradually reassembled into nanoparticles because the subunits are desorbed from the zeolites by the steric hindrance of the added PEG molecules. The present study reveals that PEGylated encapsulin was reassembled and hollow encapsulin nanoparticles were obtained. The results clearly demonstrate the usefulness of zeolites as a tool for the successful refolding of PEGylated proteins and their reassembly with tertiary structures.